PENERAPAN PENDEKATAN PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH PADA MATA PELAJARAN DASAR PENGENDALIAN MUTU HASIL PERTANIAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMK NEGERI 3 TAKALAR - Muspitasari, Risma; Irfan, Andi Muhammad; Purnamawati, Purnamawati (Jurnal Pendidikan Teknologi Pertanian, 2016)
This research is a Classroom Action Research, which aims to improve the students’ learning results of class X TPHP SMK Negeri 3 Takalar with the implementation of cooperative learning Make A Match on the lesson of basic quality control of agricultural products. Subjects of this study consisted of 39 students of class X TPHP. The data collected through observation and tests each end of the cycle in accordance with the taught material. Research procedure included the step of: (a) planning, (b) implementation, (c) observation, and (d) reflection. Data were analyzed by using quantitative data. The results of the research show that the application of cooperative learning approach type Make A Match can improve students’ learning result. This was seen in the pre-test, the first and the second cycle of students’ learning result had increased